Innovative Pathways to Net-Zero: The Role of Startups in Accelerating Circular Economy Transitions - Alqassimi, Omaima (International Review of Management and Marketing, 2025)
Startups play a pivotal role in advancing circular economy transitions and achieving sustainability goals, particularly in emerging economies like UAE. This study examines the contributions of two UAE startups, Careem and El Grocer companies, to innovation, scalability, and sustainability, providing insights into their operational dynamics and challenges. A qualitative research design was employed, incorporating semi-structured interviews, organizational document analysis, and observational data. The thematic analysis revealed key themes, including innovation and agility, sustainability practices, scaling challenges, and external influences. Careem demonstrated agility through its use of data-driven innovation and agile frameworks, enabling successful scaling and impactful sustainability practices via shared transportation models. In contrast, El Grocer faced significant operational inefficiencies and scaling challenges, despite its focus on reducing packaging waste and optimizing delivery logistics. Comparative analysis highlighted Careem’s ability to benefit from supportive policies and external funding, whereas El Grocer struggled with limited access to sector-specific support. The findings emphasize the critical role of scalable innovation and tailored support systems in enabling startups to overcome challenges and achieve systemic sustainability impacts. Recommendations include adopting agile frameworks, leveraging technology for operational efficiency, enhancing policy and funding ecosystems, and fostering collaboration across industries. This study provides valuable insights for startups, policymakers, and ecosystem enablers aiming to foster innovation and sustainability in the startup ecosystem, ultimately accelerating the transition to a resilient and circular economy.